Ecosystem R + D + i: Development of technology-based companies - Carmina Caballero, Frida; Universidad Autónoma de Tamaulipas (Libros UAT, 2019)
The information analyzed allows us to assume that Tamaulipas is in the process of strengthening the scientific and technological capabilities of the components of the R & D & I ecosystem, and of integrating a knowledge management system that guides the interactions between higher education, companies, government, society and regions that promote the development of joint programs between actors and regions, associated with the design of policies related to governance in the territory.